Are Menstrual Problems Associated with the Mental Health? A Cross Sectional Study among the Graduation College Girls - SR, Quraishi; VB, Waghachavare; AD, Gore; GB, Dhumale (IIUM Medical Journal Malaysia, 2015)
Introduction: Menstrual problems like menorrhagia, dysmenorrhea and premenstrual syndrome (PMS) are common in adolescent girls. However literature regarding association between menstrual and mental health problems is limited; hence the current study was planned. Methods: It is a cross-sectional study conducted in Sangli district (Maharashtra), India among the female students from three randomly selected graduation colleges. Calculated sample size was 605 and cluster random sampling technique was applied. The study duration was June 2013 - May 2014. Study instrument was self-administered questionnaire with inventories like PSST-A, DASS-21 and SPIN. Statistical analysis was done using chi-square test and binary logistic regression. Results: Of the 707 participants; 413 (58.4%) had menstrual problems with dysmenorrhoea being the commonest. Embarrassment due to menstruation was felt by 14.9%. Menstrual problems were associated with perceived body type, body image, stress and anxiety. Embarrassment due to menstruation was associated with social phobia, stress, anxiety and depression. On binary logistic regression; body image and embarrassment due to menstruation were significant predictors for menstrual problems. Conclusions: Menstrual problems contribute to the development of various Mental Health disturbances. Hence, girls should be encouraged to seek health advice for the menstrual problems. A full time Health counsellor in schools and colleges can justify addressing adolescent health problems.